A-value revisited: ring flip energy of chair structures in halogenated cyclohexanes by quantum chemical methods - Datta S. (2023)
A-value is conventionally defined as the ring flip Gibbs energy of chair conformers in monosubstituted cyclohexanes. It is well accepted in organic chemistry as one of the proxies of steric hindrance of a substituent group with respect to hydrogen. In this paper, the ring flip energy of mono– and dihalogenated cyclohexanes was investigated by high-level quantum chemical methods. Satisfactory agreements between calculated values and published experimental values from NMR were established before extending the concept to ring flip energies of polyhalogenated cyclohexanes. We assessed the qualitative and quantitative accuracy of prediction of ring flip energies by A-values in two models: a simple and intuitive model based on linear combinations of A-values and a proposed extension of this model to include geminal substituent interactions. The simple model results in poor predictions of ring flip energy in polyhalogenated cyclohexanes, and the extended model provides only slight improvement. Our data suggests that simple linear combination of traditional or extended A-values may not be appropriate for the energy prediction of systems in this study.